Effect of Tape on Dynamic Postural Stability in Subjects with Chronic Ankle Instability - De Ridder, R.; Willems, T. M.; Vanrenterghem, J.; Roosen, P. (International Journal of Sports Medicine, 2015)
The objective of our study was to evaluate the effect of taping on the dynamic postural stability during a jump landing protocol in subjects with chronic ankle instability (CAI). For this purpose, 28 subjects with CAI performed a sagittal and frontal plane landing task in a non-taped and taped condition. As main outcome measure, the dynamic postural stability index (DPSI) was calculated. In addition, subjective feelings of instability and perceived difficulty level were assessed. Furthermore, mechanical effectiveness of the tape on the ankle joint was determined by registering 3D kinematics. 3 subjects were excluded based on discomfort during the landing protocol. Study results indicated that the tape reduced plantar flexion and inversion at the ankle at touchdown and range of motion in the landing phase. There was, however, no effect on the DPSI or on its directional subcomponents. Subjective feelings of stability with tape improved significantly, whereas perceived difficulty did not change. In conclusion, our taping procedure did not improve postural control during a sagittal and frontal plane landing task in subjects with CAI. Perceived instability did improve and is considered an important treatment outcome, which suggests that taping could be considered as a treatment modality by clinicians.
Keywords: ankle injuries; athletic tape; postural balance; kinematics; kinetics